Służba aniołów ludziom w oparciu o "De civitate Dei" św. Augustyna - Jaśkiewicz, Sylwester (Vox Patrum, 2023)
Angelological issues take centre stage in the classic work by St Augustine, De civitate Dei. In it, the thinker from Tagaste draws a Christian portrait of angels close to people, whom he often calls holy angels (sancti angeli), our angels (nostri angeli) or good angels (angeli boni). Although the Bishop of Hippo does not omit the issue of the creation and nature of angels, he gives their function and service to people a clear priority, which is confirmed by the use of the Latin term angelus, which for him means as much as nuntius, i.e. herald, messenger. The ministry of angels for people, their ministerium is, above all, the revelation of God in the world. They are the messengers who deliver the messages given to them; they are the servants who fulfil the task entrusted to them and who present the requests of the people to God. Even if angels serve both God and people, they are not mediators because the only mediator between God and people is the Man - Jesus Christ. Heavenly spirits do not grant people their immortality and happiness, and it is not through participation with them that these supernatural gifts also become part of man. People should imitate the goodwill of the holy angels and grow in their true – and free from weakness of affection – love. The angels lead men to the full glory of the true God and oppose any sacrifices made to them. Their help in man’s spiritual struggle, especially against pride, is invaluable. The early Christian thinker also reminds us about the presence of angels on the last day, when their task will be to gather the righteous. In the final dimension of eternal life, the equality (aequalitas) of people with angels announced by Christ will be the fullness of life in God.